2023
DOI: 10.1002/pro.4631
|View full text |Cite
|
Sign up to set email alerts
|

AlphaFold predicts novel human proteins with knots

Abstract: The fact that proteins can have their chain formed in a knot is known for almost 30 years. However, as they are not common, only a fraction of such proteins is available in the Protein Data Bank. It was not possible to assess their importance and versatility up until now because we did not have access to the whole proteome of an organism, let alone a human one. The arrival of efficient machine learning methods for protein structure prediction, such as AlphaFold and RoseTTaFold, changed that. We analyzed all pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…7,8 The properties of Fold, 21 and Evolutionary Scale Modeling (ESMFold) 22 to collectively release millions of 3D protein structure predictions covering most of the proteomic databases. A survey of AlphaFold database featuring a majority of UniProtKB entries revealed around 700,000 potentially knotted proteins 23 including knot types not seen before in proteins, such as 5 1 knot, 19,24 complex knots such as 6 3 , 25 7 1 , 19,24 8 3 , 24 and even a composite knot 3 1 #3 1 19 (this one is already confirmed experimentally by Bruno da Silva et al 18 ). To our knowledge, no one has checked the AlphaFold Database from θ-curves point of view, but since structures deposited in the PDB represent less than 1% of all known proteins, it is to be expected that more complex θ-curves may exist.…”
Section: ■ Introductionmentioning
confidence: 67%
“…7,8 The properties of Fold, 21 and Evolutionary Scale Modeling (ESMFold) 22 to collectively release millions of 3D protein structure predictions covering most of the proteomic databases. A survey of AlphaFold database featuring a majority of UniProtKB entries revealed around 700,000 potentially knotted proteins 23 including knot types not seen before in proteins, such as 5 1 knot, 19,24 complex knots such as 6 3 , 25 7 1 , 19,24 8 3 , 24 and even a composite knot 3 1 #3 1 19 (this one is already confirmed experimentally by Bruno da Silva et al 18 ). To our knowledge, no one has checked the AlphaFold Database from θ-curves point of view, but since structures deposited in the PDB represent less than 1% of all known proteins, it is to be expected that more complex θ-curves may exist.…”
Section: ■ Introductionmentioning
confidence: 67%
“…The 5 1 and 7 1 knots identified by Brems et al [26] are single-domain structures with no visible dense residue packing. The 6 3 knot found by Perlinska et al [27] is a double-domain knot; however, the domains are swapped. A similar effect was already observed in the analysis of a possible evolutionary pathway of the deep 4 1 knot, another topologically symmetric structure [28], which opens the pathway for the existence of the 6 3 -knotted protein.…”
Section: Discussionmentioning
confidence: 85%
“…In this spirit, among the structures predicted by AlphaFold, Brems et al identified two new knot topologies, with five and seven crossings in minimal crossing projection (5 1 and 7 1 knots); the latter, if experimentally verified, would be the most complex protein knot to date [26]. Yet another knot type, a symmetric knot with six crossings (6 3 knot), was found in AlphaFold predictions by Perlinska et al [27]. It is worth mentioning that all of those knots, if also identified in an experiment, would disprove the long-standing hypothesis that all protein knots are formed by single threading through a twist loop (so-called "twist knots") [28].…”
Section: Introductionmentioning
confidence: 95%
“…Methods from mathematical topology can provide more accurate measurable characterization of protein structure complexity both locally and globally 19 23 . In particular, methods from knot theory enable the characterization of complexity of both unknotted and knotted proteins 21 , 23 28 . Recent work has shown a connection between novel topological metrics and protein kinetics, namely, that experimental protein folding rates correlate with the topological structural complexity of the native state of simple, 2-state proteins without knots or slipknots 23 .…”
Section: Introductionmentioning
confidence: 99%